2008
DOI: 10.1002/nbm.1316
|View full text |Cite
|
Sign up to set email alerts
|

In vivo1H MRS of WSU‐DLCL2 human non‐Hodgkin's lymphoma xenografts: response to rituximab and rituximab plus CHOP

Abstract: In order to identify early (1)H MRS metabolic markers of response to rituximab immunotherapy and to rituximab plus CHOP (cyclophosphamide, hydroxydoxorubicin, vincristine, and prednisone) combination therapy, we performed an in vivo MRS investigation of a non-Hodgkin's lymphoma (NHL) xenograft model. Human WSU-DLCL2 NHL cells were subcutaneously implanted into flanks of female severe combined immunodeficient mice. When tumor volumes reached approximately 600 mm(3), rituximab was administered for three weekly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Increased fatty acyl chain resonances in MR-visible lipids have been correlated with malignancy and necrosis in human brain tumors (33-35) and an increase in polyunsaturated fatty acids (PUFA) (36, 37), along with a decrease in lactate (38, 39), is typically observed in tumors after treatment. We observed an increase in the 1.3 ppm resonance in both untreated and treated tumors compared to baseline but increased PUFA resonance at 2.8 ppm was observed only in treated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Increased fatty acyl chain resonances in MR-visible lipids have been correlated with malignancy and necrosis in human brain tumors (33-35) and an increase in polyunsaturated fatty acids (PUFA) (36, 37), along with a decrease in lactate (38, 39), is typically observed in tumors after treatment. We observed an increase in the 1.3 ppm resonance in both untreated and treated tumors compared to baseline but increased PUFA resonance at 2.8 ppm was observed only in treated tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The product of glycolysis, pyruvate, can either be converted to acetyl-CoA and enter the tricarboxylic acid cycle or be converted to lactic acid. Lactate levels in * * * tumors can be monitored using 1 H NMR imaging, and studies have shown using this technique that response to therapy can be accompanied by decreased levels of lactic acid [27]. Thus, Lee et al [27] showed that response to treatment of xenografts derived from WSU-DLCL2 nonHodgkin's lymphoma cells with a combination of rituximab, cyclophosphamide, hydroxydoxorubicin, vincristine and prednisone exhibited decreased lactate levels.…”
Section: Discussionmentioning
confidence: 99%
“…Lactate levels in * * * tumors can be monitored using 1 H NMR imaging, and studies have shown using this technique that response to therapy can be accompanied by decreased levels of lactic acid [27]. Thus, Lee et al [27] showed that response to treatment of xenografts derived from WSU-DLCL2 nonHodgkin's lymphoma cells with a combination of rituximab, cyclophosphamide, hydroxydoxorubicin, vincristine and prednisone exhibited decreased lactate levels. On the other hand, the use of hyperpolarized 13 C-labeled pyruvate utilization [28] has shown decreased flux of the hyperpolarized 13 C label between pyruvate and lactate, corresponding with decreased FDG uptake by murine lymphoma cells after treatment for 24 h with the topoisomerase II inhibitor, etoposide.…”
Section: Discussionmentioning
confidence: 99%
“…49 Decreased lactate levels in tumours during therapy, compared with pretreatment levels, have been shown to be a useful indicator of response to therapy. 50 However, treatment of MDA-MB-468 cells with cetuximab, which was associated with decreased FDG incorporation, did not result in decreased lactate production, which suggests that monitoring tumour lactate levels is not useful for predicting response to cetuximab. As pyruvate production from glucose via glycolysis is not the only source of lactate in tumour cells, the absence of a correlation between lactate production and FDG utilisation is not unexpected.…”
Section: Discussionmentioning
confidence: 97%
“…The IC 50 dose for MDA-MB-468 cells and the IC 10 (maximum achievable inhibition) doses for MDA-MB-543 and SKBr3 treated with cetuximab for six days were 2.6, 5 and 148 µg/mL, respectively. Incorporation of FDG by SKBr3 and MDA-MB-453 cells was found to be decreased by MDA-MB468 cells using IC 50 and IC 20 doses of cetuximab for six days. Lactate production was found to be increased by MDA-MB-468 cells responding to cetuximab.…”
Section: Introductionmentioning
confidence: 96%